Implementation of Job Loss Guarantee Program in Medan City - Triani, Emi; Berlianti, Berlianti; Asbi, Erni Asneli (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this study is to analyze how the implementation of the Job Loss Guarantee Program in Medan City and the factors that influence the implementation of Government Regulation No. 37 of 2021. This research will use a qualitative research method with a descriptive approach. By using data collection techniques, namely by conducting primary data with interviews, observation and documentation and secondary data obtained from the literature. Data analysis techniques through data reduction, data presentation and conclusion drawing. The results show that the Job Loss Guarantee Program (JKP) is a new scheme in employment insurance that protects workers who lose their jobs due to termination of employment (PHK). This program is implemented by BPJS Ketenagakerjaan which provides benefits for 24 months with a 12-month contribution period. Participants must be enrolled in all BPJamsostek programs, including Work Accident Insurance, Old Age Insurance, Death Insurance, Pension Insurance, and National Health Insurance. The Medan City Government through the Manpower Office provides recommendations to laid-off workers to receive JKP benefits and forwards them to the BPJS Ketenagakerjaan Office for cash benefits. The program also includes Job Training programs for beneficiaries, job fair activities, and job market information.